1989
DOI: 10.1021/j100343a008
|View full text |Cite
|
Sign up to set email alerts
|

Infrared intensities of liquids. 5. Optical and dielectric constants, integrated intensities, and dipole moment derivatives of water and water-d2 at 22.degree.C

Abstract: We have recorded multiple attenuated total reflection spectra of liquid H20 and D20, using the Spectra-Tech CIRCLE cell, and calculated from them the infrared optical and dielectric constants and molar conductivities from 9000 to 1250 cm"1 for H20 and from 8500 to 700 cm"1 for D20. Our results agree well with the literature for H20, while our results for D20 are the most extensive reported to date. We have calculated the dipole moment derivatives with respect to stretching and bending internal coordinates from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
258
1
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(275 citation statements)
references
References 6 publications
14
258
1
1
Order By: Relevance
“…The double structure occurs also in IR spectrum of water. The IR spectrum of bulk water has also two components [89][90][91]: at about 3400 cm -1 and a weak shoulder at about 3250 cm -1 . The Raman spectrum of the bulk water in Figure 4 represents the spectrum recorded without the polarization analyzer.…”
Section: Discussionmentioning
confidence: 99%
“…The double structure occurs also in IR spectrum of water. The IR spectrum of bulk water has also two components [89][90][91]: at about 3400 cm -1 and a weak shoulder at about 3250 cm -1 . The Raman spectrum of the bulk water in Figure 4 represents the spectrum recorded without the polarization analyzer.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that H-bonding in H20 of the montmorillonite system increases with increasing water content and that H-bonding is reduced in the interlayer HzO of dehydrated montmorillonite. Bertie et al (1989) have also shown that the intensity of the H20 stretching vibrations increases with increasing H-bonding. The way that ions and H-bonding affect water molecules may be applied to clays to assist in assigning and deconvolving the complex interlayer water system.…”
Section: Molecular Water Vibrationsmentioning
confidence: 91%
“…The complex hydrogen-bonded network of liquid water accounts for many of its unusual physico-chemical properties, [1][2][3] the other important factor being quantum nuclear effects of the hydrogen atoms.…”
Section: Introductionmentioning
confidence: 99%